Pro-inflammatory mediator and cancer-associated chemokine CXCL8 as a prognostic indicator of tumor aggressiveness, angiogenesis, and disease progression with focus on therapeutic implications and recurrence monitoring - Hema Shree K; Gayathri R; Vishnu Priya Veeraraghavan; Selvaraj J; Pratibha Ramani (Oral Oncology Reports)
Background: Oral Squamous Cell Carcinoma (OSCC) is a prevalent malignancy characterized by high morbidity and mortality. Chronic inflammation within the tumor microenvironment plays a pivotal role in OSCC progression, with CXCL8 or interleukin-8 (IL-8) emerging as a significant cytokine implicated in various pro-tumorigenic processes. IL-8 promotes angiogenesis, immune evasion, and cancer cell stemness, contributing to tumor aggression and resistance to therapy. Understanding longitudinal changes in IL-8 expression provides insights into OSCC progression and treatment responses, potentially guiding personalized therapeutic strategies. Objectives: To investigate longitudinal trends in IL-8 expression among OSCC patients. To assess correlations between IL-8 levels and disease progression, treatment outcomes, and patient survival. To evaluate IL-8's prognostic value as a biomarker and its potential as a therapeutic target. Methods: A prospective longitudinal study enrolled 75 OSCC patients divided into pre-treatment, post-treatment, and follow-up groups. Saliva samples were collected, and IL-8 expression levels were quantified using RT-PCR and ELISA. Temporal trends in IL-8 expression and associations with clinical outcomes were analyzed using mixed-effects models and Kaplan-Meier survival analysis. Results: Significant elevation of IL-8 levels was observed in OSCC patients compared to controls. IL-8 levels decreased post-treatment but remained elevated compared to controls, with higher levels correlating with advanced tumor stages and poorer differentiation. Kaplan-Meier analysis demonstrated reduced survival probabilities in patients with persistently high IL-8 expression. Conclusions: Longitudinal monitoring of IL-8 expression offers valuable insights into OSCC pathogenesis and treatment response. IL-8's role as a prognostic biomarker and therapeutic target warrants further exploration to enhance disease management and patient outcomes.